The Study of Islam in Indonesia: A 75-Year Retrospective on a Post-Orientalist Collaboration - Hoesterey, James B. (Studia Islamika, 2025)
This special issue retrospective on the study of Islam in Indonesia chronicles several disciplinary approaches, methodological strategies, and theoretical interventions in the study of the social, economic, political, artistic, and religious life of Islam, across nearly eight decades of Indonesian independence. As a collection of essays in the spirit of reflection on a wide corpus of scholarship, these essays cover an incredible breadth of ground. This introduction offers some context for the intellectual vision of this panel (moving towards Post-Orientalist collaborations) and ponders possible future models of research and scholarship that are cognizant of trends in postcolonial theory and decolonial thought that seek to diversify and amplify voices on the margin, not simply for the sake of diverse representation, but especially to expand and sharpen our understandings of Islam in Indonesia.